2017
DOI: 10.1111/clr.13108
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of abutment height on interproximal implant bone level in the early healing: A randomized clinical trial

Abstract: Objective: The aim of this randomized clinical trial was to compare the effect on the interproximal implant bone loss (IBL) of two different heights (1 and 3 mm) of definitive abutments placed at bone level implants with a platform switched design. Material and methods:Twenty-two patients received forty-four implants (6.5-10 mm length and 3.5-4 mm diameter) to replace at least two adjacent missing teeth, one bridge set to each patient-two implants per bridge. Patients were randomly allocated, and two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
4
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(122 citation statements)
references
References 47 publications
(74 reference statements)
4
110
4
4
Order By: Relevance
“…have showed that monomers from resin cement can be detrimental to osteoblast‐like cells (Kraus et al., ). Several clinical studies, like Novoa et al., detected statistically significant more bone loss around 1‐mm‐height multiunit abutment, compared to 2.5 mm (Nóvoa et al., ) or 3.0 mm heights (Blanco et al., ). Similar results were presented by Galindo‐Moreno et al., revealing more bone loss if multiunit abutment was shorter than 2 mm (Galindo‐Moreno et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…have showed that monomers from resin cement can be detrimental to osteoblast‐like cells (Kraus et al., ). Several clinical studies, like Novoa et al., detected statistically significant more bone loss around 1‐mm‐height multiunit abutment, compared to 2.5 mm (Nóvoa et al., ) or 3.0 mm heights (Blanco et al., ). Similar results were presented by Galindo‐Moreno et al., revealing more bone loss if multiunit abutment was shorter than 2 mm (Galindo‐Moreno et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…The lack of cases treated by experts in this population is another possible source of bias (Cushen & Turkyilmaz, ). Many implant‐related variables such as abutment height and implant surface (Blanco et al, ; Spinato, Bernardello, Sassatelli, & Zaffe, ) or soft‐tissue thickness (Suárez‐López del Amo et al, ), which have been related to bone loss, were not evaluated. While many known patient and implant‐level factors were explored, only a small set of the most influential variables were evaluated as explanatory variables.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the Ethics Investigation Committee of Galicia (2016‐593). A similar design as in our previous publication reporting the results on the early healing of implants placed at bone level and restored with different abutments height in locations with thick mucosa was done (Blanco et al, ).…”
Section: Methodsmentioning
confidence: 97%
“…The maintenance of the initially achieved peri‐implant bone level is a key factor for long‐term success and good aesthetic results in implant therapy, and therefore, the study of factors affecting marginal bone levels around implants has gained importance over the last few years (Blanco et al, , ; Molina, Sanz‐Sánchez, Martín, Blanco, & Sanz, ; Nóvoa et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation